2012
DOI: 10.1093/ntr/ntr325
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Gene Expression Induced by Environmental Tobacco Smoke Exposure in Pregnancy

Abstract: This study demonstrates that even low dose exposure to ETS during pregnancy leads to significant deregulation of transcription in placental and fetal cells. These data suggest that the effect of ETS on the fetus is primarily indirect, mediated via deregulation of placental functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Votavova et al compared the transcriptome of the term placenta in smokers and non-smokers using a microarray analysis. Their findings demonstrated increased expression of genes related to coagulation and vasculogenesis and decreased expression of cell adhesion-related genes [19], [20]. In a recent study of the placental DNA methylation in term placentas, maternal smoking was found to deregulate the placental methylation in a CpG site-specific manner that correlated with meaningful alterations in gene expression among signature pathways [21].…”
Section: Introductionmentioning
confidence: 98%
“…Votavova et al compared the transcriptome of the term placenta in smokers and non-smokers using a microarray analysis. Their findings demonstrated increased expression of genes related to coagulation and vasculogenesis and decreased expression of cell adhesion-related genes [19], [20]. In a recent study of the placental DNA methylation in term placentas, maternal smoking was found to deregulate the placental methylation in a CpG site-specific manner that correlated with meaningful alterations in gene expression among signature pathways [21].…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies profiling gene expression by microarray analysis have shown that smoking causes significant expression changes in maternal, placental and fetal tissues, particularly in those genes involved in xenobiotic metabolism, oxidative stress, inflammation and immunity [19,20]. To our knowledge, no previous studies have explored the influence of smoking on the levels of angiogenic factors and oxidative stress in the early stages of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly contributing to impaired lung function are data that suggest that maternal smoke exposure may alter Clara cell secretory protein (CCSP) expression in fetal lungs [134]. Indeed, evidence currently suggests that maternal smoke exposure (including SHS) during pregnancy leads to the deregulation of gene expression [135]. Confirmatory primate studies have shown that in utero nicotine exposure adversely affects overall lung development by decreasing lung size and volume, elastin, while increasing Type I and Type III collagen, alveolar volume, and airway wall areas [136,137,138,139].…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%